Surgical treatment of the impingement syndrome and of the rotator cuff tears: personal experience in 134 cases - S. Candiotto; A. Majoni; L. Londei; A. Rioda; P. Ostuni (PAGEPress Publications, 2002)
The time-course covered by the original definition of scapulo-humeral periarthritis suggested by Duplay through the more recent term of subacromial impingement syndrome coined by Neer, follows the identification of the pathogenetic mechanisms leading to chronic subacromial impingement and degenerative tears of the rotator cuff. The Authors recall the functional-anatomic development evolution of the shoulder and the disequilibrium between the depressor and the elevator muscles which may promote the chronic friction against the acromion. However, the actual pathogenesis of the impingement still remains controversial. We evaluated 134 patients (81F, 53M, mean age 56.4 years) with chronic subacromial impingement syndrome. In 92 cases (69%) non traumatic tears of the rotator cuff were also present as confirmed by ultrasonography in 94 cases, CT in18 cases and magnetic resonance in 102 cases. The different tear patterns of the rotator cuff were classified as suggested by Ellman (L shaped, L reverse, triangular, trapezoidal and massive with retraction) and clinical results were analysed following Sahlstrand clinical criteria and Costant numerical scale. According to the anatomical damage, patients were divided into those with impingement without severe cuff tendinopathy (42 cases), those with rotator cuff tears without loss of motion of the shoulder (32 cases) and those with cuff tears and loss of active motion (60 cases). The different surgical techniques and rehabilitation procedures after surgery are also reported. After a mean follow-up of 1.3 years (range 8 months - 2 years), good or excellent results were obtained in 91% of the patients without rotator cuff tears, in 87% of the patients with tears but without loss of motion and in 75% of the cases with loss of active motion. Our data demonstrate that in the majority of patients with chronic impingement syndrome and rotator cuff tears, surgical treatment shows high success rates. When surgery is associated with a careful rehabilitation programme it may frequently allow patients to return to their baseline function.